TINGKAT KEBISINGAN DI INDUSTRI PENGGERGAJIAN KAYU STUDI KASUS DUA PENGGERGAJIAN KAYU DI KALIMANTAN SELATAN - Soenarno Soenarno; Maman Mansyur Idris (Jurnal Penelitian Hasil Hutan, 1988)
Wood processing  in Indonesia, especially  sawmilling  industries  have  been  increased  in the  last decade. Until 1985, about  295  sawmilling  industries   with  the production capacity  of  more  than 8,500,000 m3/year  have been installed.  These industries  have contributed   to  Indonesian   foreign  exchange  of  US$ 1,800.37  million.  In their  operations the problem of ergonomics,  such  as high noise   levels  has not  considered  yet.An   investigation  was conducted in  two  saw milling industries  in South Kalimantan   with  the  results  as follows   :Noise  level  in  the  second   industry   was  varied  from 96  to  102  dB(A),   and  in  the first  industry   was ranged from 92 to 94  dB(A).   This  difference   is due  to differences   in the  machine  lay out  and  working  space design.  Both  levels are higher than  the maximum   tolerable  noise level of 85 dB(A).Noise protection  means for workers  in the first industry  are not  required  for the time  being,  but  in  the second  industry they  are strongly  recommended.